2017
DOI: 10.4103/jehp.jehp_100_17
|View full text |Cite
|
Sign up to set email alerts
|

Composition of minerals and trace elements at Mamasani thermal source: A possible preventive treatment for some skin diseases

Abstract: INTRODUCTION:Some skin diseases are incurable and modern medicine can only control them. In addition, alternative treatment remedies including balneotherapy can be effective in improving skin conditions. However, there are only a limited number of studies on particular mineral or trace elements of mineral sources that have been identified in Iran. In this respect, the amount of minerals and trace elements in Mamasani thermal source, Fars Province, Iran, was measured using electrochemical, titration, and spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…The recent study on the beneficial impact of sulphur-rich thermal waters of Mamasani (South Iran) on many dermatoses including tinea versicolor and dermatophytic infections has reinforced its antifungal activity even in extreme dilutions [15]. The antibacterial and antifungal activities of sulphur are likely due to transformation of hydrogen sulfide (produced by sulphur-oxygen radicals interaction in deep epidermis) into pantothenic acid [15]. Topical potassium iodide exerts broad-spectrum antiseptic and disinfectant activity [16].…”
Section: Discussionmentioning
confidence: 99%
“…The recent study on the beneficial impact of sulphur-rich thermal waters of Mamasani (South Iran) on many dermatoses including tinea versicolor and dermatophytic infections has reinforced its antifungal activity even in extreme dilutions [15]. The antibacterial and antifungal activities of sulphur are likely due to transformation of hydrogen sulfide (produced by sulphur-oxygen radicals interaction in deep epidermis) into pantothenic acid [15]. Topical potassium iodide exerts broad-spectrum antiseptic and disinfectant activity [16].…”
Section: Discussionmentioning
confidence: 99%
“…T A B L E 2 Chemical analysis of mineral waters in comparison with Mamasani thermal source (Hamidizadeh et al, 2017)…”
Section: Discussionmentioning
confidence: 99%
“…Table shows that this source has acceptable physicochemical properties in comparison with other waters and it is safe for bathing. The study by Hamidizadeh et al suggested that Mamasani source can be effective in the treatment and alleviation of skin diseases and it is worthwhile to invest in this source for therapeutic purposes (Hamidizadeh et al, ). Another study found that Mamasani mineral water is similar to a Korean mineral water both of which have immunomodulatory effects because of suppressing most important cytokines in the pathogenesis of psoriasis such as lesional IL‐23 and IL‐17A (Lee et al, ).…”
Section: Sulfurous Watermentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of several predominant ions can define a classification of multi-ion waters. Classification of natural mineral waters based on temperature, fixed residue at 180 °C, and chemical composition have been reported in Table 1 [ 21 , 22 , 23 ].…”
Section: Thermal Water In Dermatologymentioning
confidence: 99%